Produção de biossurfactantes extracelulares por saccharomyces cerevisiae e sua aplicação em biorremediação - Kreling, Naiara Elisa (2017)
Biosurfactants are compounds produced by microorganisms with the ability to emulsification of oily compounds during bioremediation processes, promoting the absorption of the available carbon sources, and consequently biodegradation. Such compounds may be produced by a variety of microorganisms in industrial bioprocesses, in which the selection of suitable culture media and inducers for the production of the biocompound of interest is carried out. Saccharomyces cerevisiae is a yeast widely used in established industrial bioprocesses, such as the production of alcoholic beverages. However, the production of extracellular biosurfactants by this microorganism has not been explored. On the other hand, the use of intracellular biosurfactants is better referenced, having as a disadvantage the need for high cost unit operations in the processes of cellular disruption and extraction of the biocompound of the microbial cell. The aim of this study was to evaluate the potential of biosurfactants production by yeast Saccharomyces cerevisiae, as well as to test their application in bioremediation process of soil contaminated with biodiesel. Cultures of yeast strains that showed the best results of biosurfactant production in media with different concentrations (5, 20 and 35 g/L) of oily inducers (glycerol, diesel oil and soybean oil) were selected. The most productive strains were tested in pH (4.0, 5.5 and 7.0) and temperature (20°C, 30°C and 40°C), adaptating the microorganism strain corresponding to the best results for the next production of biosurfactants. The best condition selected was used for scaling the bioreactor in order to purify, characterize the biosurfactant and apply the biocompound (0.05%, 0.1% and 0.5%) obtained in the process for bioremediation of soil contaminated with 20% of biodiesel, also evaluating the influence of the presence of the contaminant in the retention of the contaminant in the soil, by performing tests in sterile soil. The production of extracellular biosurfactants in the cell free media was evaluated daily by the determination of the emulsifying activity of the monitoring of the surface tension. The inducers that promoted the highest production of biosurfactants were soybean oil and glycerol at concentrations of 20 g/L (4.80 UE/d) for the soybean oil inducer and 5 g/L for the inducer glycerol (4.45 UE/d). Acidification of the medium to a pH of 5.5 and cultivation at 30ºC promoted an increase in emulsion productivity (6.95 UE/d) when 5 g/L inducer glycerol was used. This condition was selected for the amplification of scale in 5 L bioreactor. In the 5 L scale, the production of biosurfactants promoted emulsification activities from 3.17 to 5.56 UE/d. Identification of the type of extracellular biosurfactant produced by mass spectrometry indicated the formation of glycolipids. In the proposed bioremediation test, the biosurfactant added in soil contaminated with biodiesel promoted the emulsification of the medium and facilitated the assimilation of the contaminant by the microorganisms independent of the added concentration, resulting in biodegradation of the contaminant by up to 56.71% at the end of 90 days of experiment, compared with 50.16% in natural attenuation. The contaminant retention in the soil was 28.74%, indicating that the adsorption effect of the contaminant on the soil can be interpreted as a biodegradation process. The values of emulsion productivity verified in this study indicate the possibility of the use of extracellular biosurfactants produced by S. cerevisiae, excluding the need for cellular disruption processes to obtain this biocompound.